KUALITAS PELAYANAN, KUALITAS PRODUK, CITRA PERUSAHAAN DAN PROMOSI DALAM MEMPENGAARUHI MINAT MENABUNG ANGGOTA KOPERASI - Cahya Amalia Rizkulillah; Happy Sista Devy; Versiandika Yudha Pratama (LP2M Universitas Bina Bangsa, 2022)
The purpose of this study is to find out whether there is an influence of service quality, product quality, company image and promotion on saving interest both partially and simultaneously. This research includes a type of quantitative research. The data used is primary data with a sample of 82 samples. The sampling technique in this study used the Simple Random Sampling technique. The study used multiple linear regression analysis and test methods with the help of SPSS 25. The results showed that the quality of service variables had a significant effect on saving interest, product quality had no significant effect on saving interest, company image had a significant effect on saving interest and promotion had a significant effect on saving interest. In addition, the results of the study also explained that the quality of service, product quality, company image and promotion together affect the interest in saving members